Estimation of the Uncertainty in Daytime Cirrus Cloud Radiative Forcing and Heating Rates due to Ice Crystal Optics - Dolinar, Erica K.; Campbell, James R.; Marquis, Jared W.; Lewis, Jasper R.; Lolli, Simone; Yang, Ping; Welton, Ellsworth J. (Journal of applied meteorology and climatology, 2025)
The uncertainties in absolute daytime top-of-the-atmosphere (TOA) net cirrus cloud radiative forcing (CRF) and radiative heating rates are estimated at five Micropulse Lidar Network (MPLNET) sites spanning the tropics to high latitudes. One year of semitransparent cirrus cloud (optical depth < 3.0 and cloud-top temperature < −37°C) measurements are subject to spectrally consistent optical properties for nine different ice crystal habits, thus providing a range of possible forcing values. The annual average absolute daytime TOA net CRF is positive at Barbados, Kanpur, and Singapore (0.59–0.67, 0.61–0.65, and 1.94–2.09 W m −2 , respectively), negative at Fairbanks (from −0.67 to −0.28 W m −2 ), and can regularly become positive or negative at Goddard Space Flight Center (GSFC) (from −0.06 to 0.32 W m −2 ). The TOA CRF depends on ice crystal shape; in particular, plates lead to relatively large absolute values that decrease for bullet rosettes and columns. Uncertainties in daytime cirrus cloud radiative properties are estimated as the standard deviation of all possible outcomes when considering the different particle habits individually. Annually, the average uncertainty of the absolute daytime TOA net CRF ranges from 0.50 to 1.80 W m −2 . In-cloud daytime net radiative heating rates are positive, on average, at all five sites (0.25–3.84 K day −1 ) and have an estimated uncertainty of less than 0.30 K day −1 . The uncertainties in cirrus radiative forcing and heating that are characterized by assumptions regarding the ice crystal optical properties must be considered in downstream applications, including satellite retrievals and numerical weather prediction.